Exploring the influence of Thai private universities human resource management practices on employee retention and performance - Chukwuemeka Nwafor, Lloyd (Edelweiss Applied Science and Technology, 2024)
The article examines employees’ perceptions regarding human resource management practices in Thai private universities. It also analyses the effects of these practices on employee job satisfaction, quality service performance and retention within the context of Thai private universities. The study employed a cross-sectional survey research approach to ensure the inclusion of a representative sample from small and medium sized private universities within the population under investigation. The study includes 12,318 employees of the 38 Thai private universities: 6,458 from small sized private universities and 5,860 from medium size private universities. 20 private universities comprised of 14 (70%) small sized and 6 (30%) will form the sample of the study. From this sample distribution, 91 (72.8) academic staff from 14 small sized private universities and 34 (27.2%) from medium sized private universities making 125 academic staff and 20 HR managers as the sample size of the investigation. The study utilized a maximum variation deliberate (MVD) sampling method for the selection of 125 academic staff and 20 HR managers. Closed-ended questionnaires and semi-structured questionnaires were employed for the purpose of data collection. The validity of the instrument was assessed by a panel of experts to establish content validity, utilizing Lawshe’s template with a ratio of 0.99. Furthermore, the homogeneity of the instrument was determined using Cronbach Alpha resulting in a reliability index of .81. The data was collected primarily via an online survey. The data underwent analysis utilizing frequency counts and percentages, chi-square at a significance level of p.05. This was done to ascertain the statistical significance of HRMP on employee retention and performance. The findings demonstrate a conspicuous and uniform association between employee responses across the institutions under scrutiny, underscoring a statistically significant connection between human resource management practices and job satisfaction, quality service performance and retention of employees. Therefore, it is essential to acknowledge that the implementation of HRM practices holds significant importance for small and medium private universities. This is primarily due to its ability to effectively address the expenses incurred from employee turnover, which can arise because of insufficient job satisfaction leading to poor job performance and retention.